Anti-Inflammatory Phytoconstituents of Origanum Majorana. (23rd May 2022) - Zhou, Li; Wang, Senye; Qu, Jiaojiao; Zhou, Huihui; Fatma, Al-Zahra K. K. Attia; Kang, Wenyi; Xi, Xuefeng; Liu, Zhenhua
Abstract : Origanum majorana belongs to the Lamiaceae family as a famous spice plant in Egypt, which is used to treat arthritis, allergies, fever, flu, hypertension, respiratory infections, migraine, and asthma. In our studies, it was found that the ethanol extract of O. marjoram could significantly reduce NO release at 200 (P < 0.001 ), 100 (P < 0.001 ) and 50 (P < 0.01 ) μ g/mL compared with the model group. Therefore, the chemical constituents were further studied to obtain the bioactive compounds. As a result, ten compounds were isolated and identified from the 70% ethanol extract of O. marjoram, including six flavonoids (3–8 ), two terpene derivatives (9-10 ), one lignan (2 ), and one phenolic glycoside (1 ). Among them, compounds 1 –3, 5, and 9-10 were isolated from this genus for the first time. Compounds 1, 9, and 10 could significantly decrease the content of NO at the concentration of 100  μ m (P < 0.001 ) in RAW264.7 cells induced by LPS. Furthermore, compounds 9 and 10 were more effective than compound 1 to lower the content at 50  μ m (P < 0.001 ).